2013
DOI: 10.1002/jgrd.50589
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of humidity measurements from global operational radiosonde sensors

Abstract: [1] The quality of humidity measurements from global operational radiosonde sensors in upper, middle, and lower troposphere for the period 2000-2011 were investigated using satellite observations from three microwave water vapor channels operating at 183.31˙1, 183.31˙3, and 183.31˙7 GHz. The radiosonde data were partitioned based on sensor type into 19 classes. The satellite brightness temperatures (Tb) were simulated using radiosonde profiles and a radiative transfer model, then the radiosonde simulated Tb's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Furthermore, the radiosonde humidity sensor can introduce systematic errors in clod and dry or cloudy conditions (Seibert et al, 2000;Moradi et al, 2013). Refractivity and specific humidity can be dominated by the water vapour pressure variations at lower altitudes, and they decrease rapidly with height von Engeln and Teixeira, 2013).…”
Section: Reasons For Discrepancies Among Different Methodsmentioning
confidence: 99%
“…Furthermore, the radiosonde humidity sensor can introduce systematic errors in clod and dry or cloudy conditions (Seibert et al, 2000;Moradi et al, 2013). Refractivity and specific humidity can be dominated by the water vapour pressure variations at lower altitudes, and they decrease rapidly with height von Engeln and Teixeira, 2013).…”
Section: Reasons For Discrepancies Among Different Methodsmentioning
confidence: 99%
“…Numerous studies on climatological trends from long-term radiosonde data records have identified difficulties with inhomogeneity within a single station's data record (e.g. Gaffen 1994;Zhang and Seidel 2011) or among data records from a subset of the global radiosonde stations (Soden and Lanzante 1996;Moradi et al 2013). Lately, several attempts for radiosonde data homogenization by statistical methods have been developed to overcome discontinuities in the station's radiosonde data record (Lanzante 1996;Gruber and Haimberger 2008;Dai et al 2011).…”
Section: Instrumentation and Data Setmentioning
confidence: 99%
“…Miloshevich et al, 2006;Moradi et al, 2013). The high quality of this setup has enabled its participation in radiosonde inter-comparison campaigns under the auspices of the World Meteorological Organization (WMO) (e.g.…”
Section: Sounding Measurementsmentioning
confidence: 99%